The Reasons and The Types of Code Switching in The Novel “Biru Pada Januari” - Nerdi, Margareta Satriana; Utami, Ni Made Verayanti; I Made Perdana Skolastika (ELYSIAN JOURNAL : English Literature, Linguistics and Translation Studies, 2022)
The purpose of this study to analyse the types and the reasons of Code Switching in the novel Biru Pada Januari. In order to identify the utterances collected from the novel “Biru Pada Januari”, this study used the theory developed by Apel and Muysken (1987:117) that distinguishes into three types of code switching, namely tag switching, inter-sentential switching, and intra-sentential switching and also the theory proposed by Hoffman (1991) about sevent reasons of Code Switching, namely talking about particular topic, expressing feeling about something, expressing group identity, interjection, repetition used for clarification, quoting somebody else, and intention of clarifying the speech content for interlocutor. And from three types of code switching inter-sentential is the dominant in the novel Biru Pada Januari and the least dominant is tag switching. Whereas from the sevent reasons the dominant types is expressing felling about something and the least is expressing group identity and intention of clarifying the speech content for interlocutor.